Peran Pancasila dalam Mengatasi Bullying di Sekolah Dasar - Nurhakim, Lukman; Subaydi; Maulidi, Rofiqi Nur (Jurnal Ilmu Pendidikan Dasar Indonesia, 2024)
This research is motivated by the high incidence of bullying among elementary school students, which negatively impacts their psychological, emotional, and academic development. The aim of this study is to understand the role of Pancasila values in mitigating bullying behavior among 5th-grade students at Juluk II Elementary School. The research employs a descriptive qualitative method, with data collected through direct observation, in-depth interviews, and document analysis. The findings reveal that the implementation of Pancasila values, such as Just and Civilized Humanity and the Unity of Indonesia, can help students develop empathy, respect for others, and resolve conflicts peacefully. These results highlight the importance of integrating Pancasila values into daily learning activities as an effort to create a safer and bullying-free school environment.